The ELPAT living organ donor Psychosocial Assessment Tool (EPAT): from 'what' to 'how' of psychosocial screening – a pilot study. (21st September 2017) - Massey, Emma K.; Timmerman, Lotte; Ismail, Sohal Y.; Duerinckx, Nathalie; Lopes, Alice; Maple, Hannah; Mega, Inês; Papachristou, Christina; Dobbels, Fabienne; ,
Summary: Thorough psychosocial screening of donor candidates is required in order to minimize potential negative consequences and to strive for optimal safety within living donation programmes. We aimed to develop an evidence‐based tool to standardize the psychosocial screening process. Key concepts of psychosocial screening1 were used to structure our tool: motivation and decision‐making, personal resources, psychopathology, social resources, ethical and legal factors and information and risk processing. We (i) discussed how each item per concept could be measured, (ii) reviewed and rated available validated tools, (iii) where necessary developed new items, (iv) assessed content validity and (v) pilot‐tested the new items. The resulting ELPAT living organ donor Psychosocial Assessment Tool (EPAT) consists of a selection of validated questionnaires (28 items in total), a semi‐structured interview (43 questions) and a Red Flag Checklist. We outline optimal procedures and conditions for implementing this tool. The EPAT and user manual are available from the authors. Use of this tool will standardize the psychosocial screening procedure ensuring that no psychosocial issues are overlooked and ensure that comparable selection criteria are used and facilitate generation of comparable psychosocial data on living donor candidates.